Implementasi Model Pembelajaran Rekreasi-Prokreasi dalam Membaca Kritis Teks Eksplanasi di SMK - Bambang Eko Hari Cahyono; Lulus Irawati; Devit Tri Candrawati (Jurusan Tadris Bahasa Indonesia, 2019)
This study aims to describe and explain (1) the conditions of critical reading learning in SMK Negeri 1 Ponorogo students, (2) the implementation of recreation-procreative learning models in learning to read critical explanatory texts, and (3) the constraints faced by teachers and students. This descriptive qualitative research uses data sources in the form of informants, events, and documents. The selected informants were Indonesian Language teachers and class XI students. Data were collected in-depth interview techniques, observation techniques, and documentation studies. Validity through extending the participation of researchers, making observations diligently and carefully, and triangulating data sources. Data analysis was performed using an interactive analysis model. The results showed that: (1) critical reading learning has not been implemented well due to the low student interest in reading, and the inaccuracy of teachers in choosing learning methods, materials, and media, (2) learning to read critical explanatory texts with recreational-procreation models can create an atmosphere new learning that is fun for students, encourages the growth and development of critical thinking skills, encourages students to express their opinions critically, and improves other language skills, (3) the obstacles faced by teachers and students, namely the lack of tools and learning media, students are less active, the teacher has not been able to become a facilitator of critical reading learning well, as well as the limited language skills of students.Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan (1) kondisi pembelajaran membaca kritis pada siswa SMK Negeri 1 Ponorogo, (2) implementasi model pembelajaran rekreasi-prokreasi dalam pembelajaran membaca kritis teks eksplanasi, dan (3) kendala-kendala yang dihadapi oleh guru dan siswa. Penelitian dengan metode deskriptif kualitatif ini menggunakan sumber data, berupa: informan, peristiwa, dan dokumen. Informan yang dipilih yaitu guru Bahasa Indonesia dan siswa kelas XI. Data dikumpulkan dengan teknik wawancara mendalam, teknik observasi, dan studi dokumentasi. Validitas melalui memperpanjang keikutsertaan peneliti, mengadakan pengamatan dengan tekun dan saksama, dan melakukan triangulasi sumber data. Analisis data dilakukan dengan model analisis interaktif. Hasil penelitian menunjukkan bahwa: (1) pembelajaran membaca kritis belum terlaksana dengan baik karena rendahnya minat baca siswa, dan kekurangtepatan guru dalam memilih metode, materi, dan media pembelajaran, (2) pembelajaran membaca kritis teks eksplanasi dengan model rekreasi-prokreasi mampu menciptakan suasana pembelajaran baru yang menyenangkan bagi siswa, mendorong tumbuh kembang kemampuan berpikir kritis, mendorong siswa berani mengemukakan pendapat secara kritis, dan meningkatkan kemampuan berbahasa lainnya, (3) kendala-kendala yang dihadapi guru dan siswa, yaitu kurang tersedianya alat dan media pembelajaran, siswa kurang aktif, guru belum mampu menjadi fasilitator pembelajaran membaca kritis secara baik, serta terbatasnya kemampuan berbahasa siswa.